2010
DOI: 10.1021/la101123y
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembly of Poly(lactic acid) Nanoparticles: A Facile Way to Fabricate Films for Model Drug Delivery

Abstract: Layer-by-layer (LBL) films of poly(lactic acid) nanoparticles (PLA NPs) and poly(ethyleneimine) (PEI) were fabricated as a novel drug-delivery system. The PLA NPs, which encapsulated pyrene as a model drug, were prepared by nanoprecipitation methods. The assembly process of PLA NPs/PEI LBL films was monitored by UV-vis spectroscopy, and the load of pyrene in the multilayer films was verified by fluorescence spectroscopy. The morphology of the PLA NPs/PEI LBL films was observed by SEM. The release profile of py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The finding can be explained by the slightly negatively surface charge of PLA, due to the presence of residual carboxyl groups, that may electrostatically repel the MMT clay. 35 Hence, from the point of building a multilayer coating on a PLA film, it is clear that the presence of a polycation is required as the primary layer on the PLA film. A polymer other than PLA is also needed in-between the MMT layers to build successfully the multilayer structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The finding can be explained by the slightly negatively surface charge of PLA, due to the presence of residual carboxyl groups, that may electrostatically repel the MMT clay. 35 Hence, from the point of building a multilayer coating on a PLA film, it is clear that the presence of a polycation is required as the primary layer on the PLA film. A polymer other than PLA is also needed in-between the MMT layers to build successfully the multilayer structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a result, the release rate increased gradually . Jiao et al fabricated poly(lactic acid) nanoparticles, which encapsulated pyrene as a model drug, and poly(ethylene imine) (PEI) LbL films as a novel drug‐delivery system. There was an initial burst in the first 20 h. They suggested that the films of poly(lactic acid) nanoparticles were promising for the sustained release of drugs.…”
Section: Resultsmentioning
confidence: 99%
“…The general concept of multilayer formation is electrostatic attraction, and it has been expanded to alternating films stabilized by hydrogen bonding, covalent bonding, hydrophobic interactions, and molecular recognition . A large number of components can be used to fabricate multilayer assemblies, including water‐soluble polyelectrolytes, natural polymers (e.g., DNA, RNA, proteins, peptides, enzymes, and polysaccharides), and advanced materials (e.g., synthetic polymers, dendritic molecules, and nanoparticles) …”
Section: Introductionmentioning
confidence: 99%
“…Figure 12 shows a number of these polyelectrolytes. The layer-by-layer method can also employ a wide range of charged components including proteins [101,102], viruses [16], nanoparticles [103][104][105], and flaky minerals [106,107]. A number of layer-by-layer methods employ interactions such as hydrogen bond [16,[108][109][110][111] or covalent bond [112][113][114][115].…”
Section: Growth Mechanisms and Structure Of Polyelectrolyte Filmsmentioning
confidence: 99%